Spiral of Silence Theory Versus Perkembangan Masyarakat suatu Penjelasan dan Kritik Teori - Hendra, Yan (Universitas Medan Area, 2019)
The Spiral of Silence Theory put forward by Elisabeth Noelle-Neumann suggests a person's reluctance to express their opinions which may not be the same as those of most people. In the course of time, this theory continues to undergo a testing process when the theory is used by academics and the general public to explain, predict, explain the phenomenon of communication that continues to grow and vary. Along with advances in communication and information technology and the emergence of various forms of new media has an impact on the increasing courage of people in expressing their opinions that are different from the opinions of most people. In this condition, the Spiral Silence Theory is not able to completely and accurately explain the phenomenon of communication of concern. This proves that the theory has limitations in explaining the phenomenon. This weakness is opening the way for experts to give birth to new ideas in modifying theories and giving birth to new theories. A theory that can no longer explain the phenomenon completely will turn the theory into an assumption.